Pengaruh Media Interaktif Aplikasi AR-QU Berbasis Augmented Reality terhadap Keterampilan Membaca Huruf Hijaiyah dan Makharijul Huruf di SDN 05 Air Tawar Barat - Yosima Nur Ilma; Rilliandi Arindra Putawa (Lembaga Yasin AlSys, 2026)
Learning hijaiyah letters and makharijul huruf has become a focus in several previous studies; however, research that specifically discusses the effectiveness of Augmented Reality-based interactive media in improving elementary school students’ reading skills remains limited. This study aims to analyze the effect of using the AR-Qu interactive application based on Augmented Reality on students’ reading skills in hijaiyah letters and makharijul huruf. This study employed a quantitative approach with a quasi-experimental design, involving 56 students selected through the total sampling technique. Data were collected through practical tests in the form of pretests and posttests, observation, and documentation, and were then analyzed using the Mann–Whitney U test and N-Gain analysis. The results show that there was a significant difference between the experimental class and the control class, with a significance value of 0.007 < 0.05. In addition, the average N-Gain score of the experimental class was 0.9912, which was in the high category, while that of the control class was 0.6856, which was in the moderate category. These findings contribute to the development of multimedia-based learning studies, particularly the use of Augmented Reality to improve understanding of abstract concepts in Qur’anic learning. The conclusion of the study emphasizes that Augmented Reality-based interactive media is effective in improving students’ reading skills in hijaiyah letters and makharijul huruf. The practical implication is that teachers and educational institutions need to consider integrating Augmented Reality technology into the learning process so that learning activities become more effective, interactive, and engaging.